The Power of Access in Parkinson's Disease Care: A Retrospective Review of Telehealth Uptake During the COVID-19 Pandemic - Falconer, Drew; Gow, Sonia; Whitney, David; Walters, Hannah; Rogers, Sean (Frontiers in Neurology, 2022)
OBJECTIVE: The onset of the COVID-19 pandemic in March of 2020 forced a rapid pivot to telehealth and compelled a use-case experiment in specialty telehealth neurology movement disorders care. The aims of this study were to quantify the potential benefit of telehealth as an option to the Parkinson’s disease community as shown by the first 9 months of the COVID-19 pandemic, and to quantify the potential impact of the absence of a deep brain stimulation (DBS) telehealth option on DBS patient follow-up. METHODS: New patient visits to the Inova Parkinson’s & Movement Disorders Center from April to December 2020 (9 months) were retrospectively reviewed for telehealth versus in-person, demographics (age, gender, race, primary insurance), chief complaint, prior movement disorders specialist (MDS) consultation, imaging tests ordered, and distance/travel time from primary zip code to clinic. Additionally, DBS programming visit volume from April to December 2020 was compared to DBS programming visit volume from April to December 2019. RESULTS: Of the 1,097 new patients seen, 85% were via telehealth (N=932) and 15% in person (N=165). In the telehealth cohort, 97.75% had not consulted with an MDS before (N=911), versus 87.9% in-person (N=145). Age range was 61.8 +/- 17.9 years (telehealth), 68.8 +/- 16.0 years (in-person). Racial breakdown for telehealth was 60.7% White (N=566), 10.4% Black (N=97), 7.4% Asian (N=69) and 4.5% Hispanic (N=42); in-person was 70.9% White (N=117), 5.5% Black (N=9), 7.9% Asian (N=13) and 5.5% Hispanic (N=9). Top 5 consultation reasons, top 10 primary insurance providers and imaging studies ordered between the two cohorts were similar. Distance/travel time between primary zip code and clinic were 33.8 +/- 104.8 miles and 42.2 +/- 93.4 minutes (telehealth) versus 38.1 +/- 114.7 miles and 44.1 +/- 97.6 minutes (in-person). DBS programming visits dropped 24.8% compared to the same period the year before (254 visits to 191 visits). CONCLUSION: Telehealth-based new patient visits to a Movement Disorders Center appeared successful at increasing access to specialty care. The minimal difference in supporting data highlights the potential parity to in-person visits. With no telehealth option for DBS visits, a significant drop-off was seen in routine DBS management.